Lynching and spectacle : witnessing racial violence in America, 1890-1940 - Wood, Amy Louise, 1967- (New directions in southern studies., 2009)
By examining lynching spectacles alongside both traditional and modern practices and within both local and national contexts, Wood reconfigures our understanding of lynching's relationship to modern life. --from publisher description.